Breaking the 10% Efficiency Barrier in Organic Photovoltaics: Morphology and Device Optimization of Well‐Known PBDTTT Polymers. Issue 11 (7th March 2016) - Zhang, Shaoqing; Ye, Long; Hou, Jianhui
Abstract : With the advances in organic photovoltaics (OPVs), the invention of model polymers with superior properties and wide applicability is of vital importance to both the academic and industrial communities. The recent inspiring advances in OPV research have included the emergence of poly(benzodithiophene‐co‐thieno[3, 4‐b]thiophene) (PBDTTT)‐based materials. Through the combined efforts on PBDTTT polymers, over 10% efficiencies have been realized recently in various types of OPV devices. This review attempts to critically summarize the recent advances with respect to five well‐known PBDTTT polymers and their design considerations, basic properties, photovoltaic performance, as well as device application in conventional, inverted, tandem solar cells. These PBDTTT polymers also make great contributions to the rapid advances in the field of emerging ternary blends and fullerene‐free OPVs with top performances. Addtionally, new challenges in developing novel photovoltaic polymers with more superior properties are prospected. More importantly, the research of highly efficient PBDTTT‐based polymers provides useful insights and builds fundamentals for new types of OPV applications with various architectures. Abstract : Well‐known PBDTTT polymers are the subject of considerable attention in the field of organic photovoltaics (OPVs). These photovoltaic polymers possess excellent absorption and hole mobility and show great potential in single‐ or multiple‐junction, ternary blend, and fullerene‐free OPV devices. Owing to the integrated morphology and device efforts, over 10% efficiencies have been realized in these novel OPV devices.